ANALISIS PENERAPAN SERTIFIKAT ELEKTRONIK DI KANTOR PERTANAHAN KABUPATEN SORONG - Rahayu, Dini; hujriman (Muadalah : Jurnal Hukum, 2025)
The implementation of electronic certificates is part of the effort to digitize the land administration system to improve efficiency, security, and transparency in land rights management. This study aims to analyze the implementation of electronic certificates at the Sorong Regency Land Office and the obstacles encountered. The methods used were observation and interviews. The results of this study indicate that the main obstacles in implementing this system include mismatches in owner data between ID cards (KTP) and analog certificates, as well as the relatively time-consuming validation process for land books and measurement letters. Nevertheless, electronic certificates provide benefits such as increased service efficiency, improved data security, and improved land transactions. To optimize their implementation, accelerated digitalization, simplified procedures, increased outreach, and strengthened regulations are needed. With these steps, the electronic certificate system can become a modern solution for land administration in Indonesia.